PRINSIP PENDIDIKAN KRISTEN DALAM KELUARGA MENURUT ULANGAN 6: 4-9 - Maria Widiastuti (JURNAL PIONIR, 2020)
This article is a literature investigation, which focuses on the discussion of the principles of Christian education in the family. There are 3 Principles of Christian Religious Education in Deuteronomy 6: 4-9: First, being a role model. As parent, what we do in life become teaching material for the children. We love God in daily life without realizing it has planted the seeds of faith in their children.  Second, Teach Repeatedly.  The instructions are the subject of conversations both inside and outside the house, from morning to night.  The commandments penetrate every area of human life.  Third, Teaching Covers All Aspects of Life.  God wants parents to teach the truth of God's word in all aspects of life.  So that children's faith is not swayed by the influence of the environment around them and remains fully dependent on the one God. Keywords: principles of Christian education in the family